1976
DOI: 10.2136/sssaj1976.03615995004000010016x
|View full text |Cite
|
Sign up to set email alerts
|

The Slow Reaction which Continues After Phosphate Adsorption: Kinetics and Equilibrium in Some Tropical Soils

Abstract: Dissolved phosphate was mixed with topsoil samples, and the decline in solution phosphate concentration (P) was followed for 200–300 days by periodically shaking and extracting subsamples with 1 or 10 mM CaCl2 (1:10).During the first 20–40 days, (P) declined faster in soil suspensions that were being shaken than it did in undisturbed soil at 0.1 bar moisture. After 40 days of reaction, shaking time had little effect.The slow fixation had first‐order kinetics with respect to (P). The relative rate was faster in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 0 publications
7
48
0
2
Order By: Relevance
“…Firstly, the reaction has been associated with the formation of amorphous coatings containing P on the surface of the adsorbents (Rajan and Fox, 1972). Secondly, it has been suggested that molecular rearrangement of the adsorbed P occurs leading to the development of a new more strongly adsorbed phase on the surface (Munns and Fox, 1976). Thirdly, the absorbent dissolves leading to the precipitation of amorphous and crystalline phosphate (Van Riemsdijk and Lyklema 1980).…”
Section: Reactions Of Phosphorus In Soilmentioning
confidence: 99%
“…Firstly, the reaction has been associated with the formation of amorphous coatings containing P on the surface of the adsorbents (Rajan and Fox, 1972). Secondly, it has been suggested that molecular rearrangement of the adsorbed P occurs leading to the development of a new more strongly adsorbed phase on the surface (Munns and Fox, 1976). Thirdly, the absorbent dissolves leading to the precipitation of amorphous and crystalline phosphate (Van Riemsdijk and Lyklema 1980).…”
Section: Reactions Of Phosphorus In Soilmentioning
confidence: 99%
“…Past research has shown that the reaction of P with soils is not instantaneous. The first stage proceeds relatively rapidly and this is followed by a slower sorption phase which continues for a long time (Rajan & Fox 1972;Chen et al 1973;Munns & Fox 1976;Ryden et al 1977;Ibrahim & Pratt 1982;Bolan et al 1985). An equilibrium state may or may not be reached.…”
Section: Introductionmentioning
confidence: 99%
“…** Fax no: +9167524361 in a week, where P is adsorbed to the soil surfaces. The second is a slow reaction resulting in a continued, long-term decline of P in soil solution (Munns and Fox, 1976). Although the mechanism for the slow reaction is not well understood, its influence on residual P effectiveness is important in developing efficient long-term management strategies (Munns and Fox, 1976).…”
Section: Introductionmentioning
confidence: 99%